2010
DOI: 10.1093/jmcb/mjq006
|View full text |Cite
|
Sign up to set email alerts
|

20-hydroxyecdysone Reduces Insect Food Consumption Resulting in Fat Body Lipolysis During Molting and Pupation

Abstract: The insect steroid hormone 20-hydroxyecdysone (20E) acts through a specific nuclear receptor complex, ecdysone receptor (EcR) and ultraspiracle (USP). EcR and USP are FXR/LXR and RXR orthologs, respectively, which play critical roles in the regulation of lipid metabolism in mammals. Lipid concentration in Bombyx hemolymph and lipase activity in fat body peaked during molting and pupation, suggesting that 20E induces lipolysis at these stages. Differing from their mammalian orthologs, the 20E-bound EcR-USP was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 63 publications
8
54
0
Order By: Relevance
“…In Bombyx, 20E slowly reduces food consumption and then induces starvationlike conditions during molting and pupation, providing a correlation between 20E and starvation in the induction of both autophagy and apoptosis. 31 In a previous study, we have found that autophagy precedes apoptosis in the midgut during Bombyx metamorphosis, but the core mechanism is not illustrated. 40 Here, we found that starvation and 20E addition caused significant cell death after 4 to 16 h treatment, with autophagy proceeding apoptosis at least by 3 h in Bombyx Bm-12 cells (Figs.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…In Bombyx, 20E slowly reduces food consumption and then induces starvationlike conditions during molting and pupation, providing a correlation between 20E and starvation in the induction of both autophagy and apoptosis. 31 In a previous study, we have found that autophagy precedes apoptosis in the midgut during Bombyx metamorphosis, but the core mechanism is not illustrated. 40 Here, we found that starvation and 20E addition caused significant cell death after 4 to 16 h treatment, with autophagy proceeding apoptosis at least by 3 h in Bombyx Bm-12 cells (Figs.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, a long period of starvation caused degradation of ATG8 in S1-HP cells under amino acid starvation (S. litura), 44 it appears the same case in Bm-12 cells at 16 h after starvation consistent with the change of LysoTracker Red staining. In vivo, 20E induces starvation-like condition in a complex manner; 31,43,45 in turn, starvation induces autophagy and apoptosis. These phenomena could explain why both 20E and starvation causes massive cell death in the larval midgut during Bombyx metamorphosis, with autophagy preceding apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations